2020
DOI: 10.1039/d0sc03299a
|View full text |Cite
|
Sign up to set email alerts
|

Seeing luminescence appear as crystals crumble. Isolation and subsequent self-association of individual [(C6H11NC)2Au]+ions in crystals

Abstract: Non-luminescent, isostructural crystals of C6H6•[(C6H11NC)2Au](EF6) (E = As, Sb] lose benzene upon standing in air to produce green luminescent (E = As) or blue luminescent (E = Sb) powders.  Previous studies...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Away from the mother liquor, they crack and crumble, presumably due to the loss of volatile solvate molecules. Solvate loss from crystals is a serious issue that can alter not only composition but also structure and properties . The low solubility and solution instability of these crystals preclude characterization by liquid-phase techniques such as NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Away from the mother liquor, they crack and crumble, presumably due to the loss of volatile solvate molecules. Solvate loss from crystals is a serious issue that can alter not only composition but also structure and properties . The low solubility and solution instability of these crystals preclude characterization by liquid-phase techniques such as NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The acceptor orbital comprises a 4p orbital on the copper ion, with bonding overlap with the primarily 6p orbitals on the gold ion. This suggests that the excitation increases the strength of the Au–Cu metal–metal bonding interaction in the excited state, a hallmark of metallophilic luminescence. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…− counterion effect in the reconstruction and rearrangement of Au(I)-based complexes. 49,50 In many relevant cases, excess SbF 6 − counterions are required to reach the steady state of metal clusters. 48−50 However, the whole-segment monitoring of this reconstruction of metal nanoclusters in the presence of SbF − counterion effects are evaluated from two aspects: the reconstruction of nanocluster structures, which refers to the molecular chemistry, and the rearrangement of crystalline cluster molecules, which touches upon the supramolecular chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is plausible that the control over counterions serves as another efficient approach to manipulate the intra- or intercluster architectures of metal nanoclusters and to dictate their physical–chemical properties as investigated by us, Lee’s, and Pradeep’s groups. In general, most counterions (e.g., TOA + , PPh 4 + , BPh 4 – , and so on) have a minor impact on intracluster architectures but can remarkably influence their packing modes in the supracrystal lattice. The SbF 6 – counterion, by contrast, is unique in this respect: the interaction between its F terminals and surface metals in nanoclusters can induce both the reconstruction of intracluster structures and the rearrangement of cluster molecules in the supracrystal lattice. Chen et al reported the Ag–F interaction-triggered intercluster connection in the crystal lattice, and the Balch group presented several cases of the SbF 6 – counterion effect in the reconstruction and rearrangement of Au­(I)-based complexes. , In many relevant cases, excess SbF 6 – counterions are required to reach the steady state of metal clusters. However, the whole-segment monitoring of this reconstruction of metal nanoclusters in the presence of SbF 6 – remains challenging, and the research of SbF 6 – counterion effect in regulating the physical–chemical properties of nanoclusters is still limited up to the present, which impedes the in-depth understanding of the SbF 6 – counterion effect in the cluster science.…”
Section: Introductionmentioning
confidence: 99%